A Color Map for Pseudo Color Processing of Medical Images - B, Selvapriya; B, Raghu (International Journal of Engineering and Technology, 2018)
A color map is one which converts theÂ colorsÂ of one image to theÂ colorsÂ of another image. This paper says about a color map for pseudocoloring of medical image which converts gray scale medical images to color with the already existing color map. Converting a black and white image to color has no correct way or method, this method provides a direct way to choose, Red, Green and Blue (RGB) colors to individual components, but the color map conversion is done by converting the entire gray-scale image to color. By creating a color map then the color map is to be used to color the medical gray scale image. This method is applied for gray scale medical images such that the perception and quality of the image can be improved.Â Â